Onset-related subtypes of Parkinson's disease differ in the patterns of striatal dopaminergic dysfunction: A positron emission tomography study. Issue 12 (December 2015) - Liu, Shu-Ying; Wu, Jian-Jun; Zhao, Jue; Huang, Si-Fei; Wang, Yi-Xuan; Ge, Jing-Jie; Wu, Ping; Zuo, Chuan-Tao; Ding, Zheng-Tong; Wang, Jian
Abstract: Purpose: The young-onset subtype of Parkinson's disease (YOPD) differs from the late-onset subtype (LOPD) in drug responsiveness, incidence of motor complications, and prognosis. The pathophysiology underlying these differences remains largely unknown. This study investigated whether the two subtypes differ in the pattern of dysfunction in striatal (caudate and putamen) dopaminergic system and if the dopamine transporter (DAT) imaging patterns are associated with the clinical features of corresponding PD subtype. Methods: We assessed the spatial pattern of striatal dopaminergic dysfunction in 40 YOPD and 47 LOPD with early to mid-stage PD with DAT imaging by positron emission tomography. Two sub-regional parameters (caudate/putamen ratio and asymmetry index) were calculated to measure the spatial pattern of striatal dopaminergic dysfunction. Results: The caudate/anterior putamen ratios were significantly higher in YOPD than that in the LOPD ( P = 0.03 contralateral to the most affected side of the body and P = 0.004 ipsilateral), which was supported by significantly inverse correlations between age of onset and caudate/anterior putamen ratios (r = −0.428, P < 0.001 for the contralateral and r = −0.576, P < 0.001 for the ipsilateral). Sub-regional DAT binding in caudate ipsilateral to affected limbs was significantly correlated with age, while DAT bindings in putamen were significantly inversely correlated with disease duration and UPDRS motor scores. Conclusion: The YOPD subtype suffers from an uneven pattern of dopaminergic dysfunction: more sparing of the caudate compared with the putamen, while the LOPD patients is with a relatively uniform pattern. Highlights: Striatal patterns of dopaminergic degeneration were examined with [ 11 C]-CFT PET in YOPD and LOPD. The DAT pattern of YOPD showed more sparing of caudate compared with putamen. The DAT pattern of LOPD showed relatively uniform involvement of both caudate and putamen. YOPD and LOPD were similar in contralateral-ipsilateral asymmetry. Different DAT patterns of YOPD and LOPD may fit basal ganglia-thalamocortical circuitry.